2020
DOI: 10.1101/2020.10.05.325985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trans-generational inheritance of centromere identity requires the CENP-A N-terminal tail in theC. elegansmaternal germ line

Abstract: Centromere protein A (CENP-A) is a histone H3 variant that defines centromeric chromatin and is essential for centromere function. In most eukaryotes CENP-A-containing chromatin is epigenetically maintained, and centromere identity is inherited from one cell cycle to the next. In the germ line of the holocentric nematode Caenorhabditis elegans, this inheritance cycle is disrupted. CENP-A is removed at the mitosis-to-meiosis transition and is established de novo on chromatin during diplotene of meiosis I. Here … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…C. elegans germ cells move through the gonad from distal to proximal zone as they progress through meiosis. CENP-A and KNL-2 are present on chromatin in the mitotically proliferating zone (distal zone), then they are removed at the onset of meiosis (transition zone) and associate with chromatin again in diplotene (proximal zone) (Gassmann et al, 2012; Maddox et al, 2007; Prosée et al, 2020). We investigated chromosome morphology in the S772A/S784A meiotic germ cells and found that it was altered in the proximal zone of the germ line, but seemed unaffected in the pachytene zone (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…C. elegans germ cells move through the gonad from distal to proximal zone as they progress through meiosis. CENP-A and KNL-2 are present on chromatin in the mitotically proliferating zone (distal zone), then they are removed at the onset of meiosis (transition zone) and associate with chromatin again in diplotene (proximal zone) (Gassmann et al, 2012; Maddox et al, 2007; Prosée et al, 2020). We investigated chromosome morphology in the S772A/S784A meiotic germ cells and found that it was altered in the proximal zone of the germ line, but seemed unaffected in the pachytene zone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that condensin II achieves a stable chromatin association during prophase in human cells (Gerlich et al, 2006), we favour the hypothesis of condensin II being less efficiently recruited to chromatin in the S772A/S784A strain. It has recently been observed that when KNL-2 loses its interaction with CENP-A, it fails to localise to chromatin, and chromosome condensation becomes defective (Prosée et al, 2020). This suggests that KNL-2 chromatin association precedes condensin II recruitment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, whether the N-tail-KNL-2 interaction reported here continues to be required to load CENP-A HCP-3 after de novo loading in the first embryonic division is an important question. A recent study reported that embryos homozygous mutant for N-tail deleted CENP-A HCP-3 , derived from a heterozygous parent and thus having maternally loaded fulllength CENP-A HCP-3 , developed into adults; by contrast, embryos homozygous null mutant for CENP-A HCP-3 derived from a heterozygous parent did not (Prosée et al, 2020). This observation indicates that the N-tail deleted CENP-A HCP-3 supports development following depletion of maternally loaded full-length CENP-A , suggesting that the N-tail may not be essential for loading later in embryogenesis.…”
Section: Discussionmentioning
confidence: 99%